Situational Awareness Training Evaluation with Computer Based Test for Pilot Cadet - Hariri, Ahmad; Parjan; Rubiono, Gatut; Cahyo, Dimas Hari (World Journal of Vocational Education and Training, 2022)
Situational awareness (SA) is the most important category in single pilot resource management. SA is how a pilot assesses the situation inside and outside the aircraft appropriately to achieve safe and efficient flight safety. SA is an important constituent of a person in information processing and the pilot decision-making process. This study aims to evaluate training in cadet situation awareness. The analysis was based on the aptitude test results as flight training series consisting theoretical stages, simulator and flight practices. Aptitude test is consisting several sections. There were pre-tests and post-tests. Aptitude test results are displayed as cadet score graph, for each section, and the final score will be approached by regression line. Each section average value and the final score are calculated to get changes level in the test score. The results showed an increase in the situational awareness of the cadets based on the aptitude test score.